THE EFFECTIVENESS OF SUBSTANTIATING THE SCIENTIFIC HERITAGE OF OUR GREAT SCIENTISTS IN THE FORMATION OF SCIENTIFIC EDUCATION OF STUDENTS OF PEDAGOGICAL UNIVERSITIES - Hotamov, Jaxongir; Bobonazarov, Dilshod; Eshpulatov, Nodir (Физико-технологического образование, 2021)
This article reflects the scientific heritage of our great thinkers and the use of this heritage in the education of students, as well as the formation of national pride in the student and its importance in scientific education.